Molecular Characterization of Anopheles sacharovi Based on Sequences of ITS2-rDNA Region and COI Gene in North of Iran - Sahereh Gholami; Hasan Bakhshi; Seyyed Hassan Moosa-Kazemi; Alireza Zahraei-Ramazani; Alireza Chavshin; Mohammad Mehdi Sedaghat (Tehran University of Medical Sciences, 2018)
Background: Malaria is an important mosquito-borne disease considered as one of the public health concerns across many countries. Anopheles mosquitoes are the main vectors of Plasmodium parasites, which cause malaria. Some of these vectors such as Anopheles maculipennis s.l. and Anopheles sacharovi are considered as complex of sibling species distributed in north of Iran. Methods: This study was conducted in north and northwest of Iran including East Azerbaijan, West Azerbaijan, Ardabil, Golestan and North Khorasan provinces with emphasis on the northern borders of the country during 2015-2016. Adult specimens were collected and subjected to morphological identification as well as molecular analysis. Results: Overall, 10405 mosquitoes were collected comprising 21 species. Culex pipiens and Cx. theileri were found as the most frequent species in whole study area. Morphological identification showed that out of 1455 female Anopheles specimens, 77% belonged to An. maculipennis Group. Out of the identified species, ITS2 region and COI gene sequences of 8 An. maculipennis s.s. and 31 An. sacharovi representing all provinces were obtained and submitted to GenBank. The COI sequences for An. sacharovi revealed the presence of 9 haplotypes with similarity of 98.17-100%. Conclusion: Some investigations have reported An. martinius as a member of sibling species of An. sacharovi among Iranian Anopheles genus; while based on our study, there was no evidence of the presence of this species in north and northwest of Iran.